Reversal of docetaxel resistance in prostate cancer by Notch signaling inhibition. Issue 9 (October 2018) - Qiu, Shi; Deng, Linghui; Bao, Yige; Jin, Kun; Tu, Xiang; Li, Jiakun; Liao, Xinyang; Liu, Zhenhua; Yang, Lu; Wei, Qiang
Abstract : Acquired docetaxel (Doc) resistance in hormone-refractory prostate cancer (HRPC) remains an ongoing clinical challenge, resulting in failed chemotherapy and tumor recurrence. However, the mechanism of Doc-resistance development in prostate cancer cells is still unclear. Here, we observed a subpopulation of prostate cancer cells, in both Doc-resistant cell lines and the tumors of patients with HRPC, which show stem cell markers and greater tumorigenic potential. Those stem-like prostate cancer cells show high expression of ABCB1, which encodes multidrug resistance-related protein P-glycoprotein, leading to the Doc-resistance in prostate cancer. Moreover, we found that Notch signaling pathway activation in Doc-resistant cell lines and tumor tissues of patients with HRPC correlated with tumorigenicity and the development of Doc resistance. Here, we revealed that a combination of Doc and a Notch signaling inhibitor overcomes Doc resistance and increases the survival of mice with Doc-resistant xenografts. Therefore, targeting the Notch signaling pathway may be a promising strategy to overcome the Doc-resistant cancer in the clinic.